Influence of soft tissues on mandibular gray scale levels - Souza,Paulo Henrique Couto (2004)
The purpose of this study was to analyze the gray levels, expressed in pixels, of the mandibular retromolar region, with regard to the influence of muscular and fat soft tissues near this region. Fifteen dry mandibles were X-rayed with the presence of soft tissue simulators. The radiographs were digitized and evaluated by Digora® software. A one cm thick layer of wax was used as a simulator of the muscular soft tissue. Animal fat samples of different thicknesses - 0.5, 1.0, 1.5 and 2.0 cm - were used as a simulator of the fat soft tissue. Results showed that the fat soft tissue simulator influenced the gray level values in pixels of the mandibular retromolar region when analyzed in different thicknesses using the Digora® digitized image software.